Оценка функционального состояния сердечно-сосудистой системы спортсменов различной квалификации, специализирующихся в беге на короткие дистанции - Криворученко, Е.; Kryvoruchenko, O. (Східноєвропейський національний університет ім.Лесі Українки, 2012)
Задача исследования − совершенствование оценки функционального состояния сердечно-сосудистой системы бегунов на короткие дистанции путем выявления информативных показателей ритмокардиографии спортсменов. В исследовании участвовали 75 квалифицированных спортсменов (мужчины), специализирующихся в беге на короткие дистанции. Представлены результаты корреляционного анализа показателей ва-риабельности сердечного ритма спортсменов различной квалификации, специализирующихся в беге на короткие дистанции. Выявлены информативные показатели ритмокардиографии бегунов на короткие дистанции с учетом спортивной квалификации и рекомендовано анализировать их во время оценки функционального состояния сердечно-сосудистой системы легкоатлетов. Независимо от спортивной квалификации бегунов на короткие дистанции в большей степени процент взаимосвязей между физической подготовленностью и показателями ритмокардиографии, регистрируемые после стандартной физической нагрузки. The task of the research is perfection of estimation of functional state of cardiovascular system of sprinters by the exposure of informing indexes of sportsmen’s rhythmocardiography. 75 skilled sportsmen that are specialized in sprint participated in the research. The results of cross-correlation analysis of indexes of variableness of cardiac rhythm of sportsmen of different qualifications, specialized sprint are presented. The informing indexes of rhythmocardiography sprinters are educed taking into account their sports qualifications and it is recommended to analyze them while the estimation of functional state of cardiovascular system of athletes. Regardless of sports qualification of short distance runners in greater degree percent of intercommunications between physical preparedness and indexes of rhythmocardiography registered after standard physical activity.
Estimation of Functional State of Cardiovascular System of Sportsmen of Different Qualifications Specialized in Sprint.
Keywords: бегуны на короткие дистанции; ритмокардиография; функциональное состояние; short distance runners; rhythmocardiography; functional state